New Insights on Leucine-Rich Repeats Receptor-Like Kinase Orthologous Relationships in Angiosperms - Dufayard, Jean-François; Bettembourg, Mathilde; Fischer, Iris; Droc, Gaetan; Guiderdoni, Emmanuel; Périn, Christophe; Chantret, Nathalie; Diévart, Anne (Frontiers in Plant Science, 2017)
Leucine-Rich Repeats Receptor-Like Kinase (LRR-RLK) genes represent a large and complex gene family in plants, mainly involved in development and stress responses. These receptors are composed of an LRR-containing extracellular domain (ECD), a transmembrane domain (TM) and an intracellular kinase domain (KD). To provide new perspectives on functional analyses of these genes in model and non-model plant species, we performed a phylogenetic analysis on 8,360 LRR-RLK receptors in 31 angiosperm genomes (8 monocots and 23 dicots). We identified 101 orthologous groups (OGs) of genes being conserved among almost all monocot and dicot species analyzed. We observed that more than 10% of these OGs are absent in the Brassicaceae species studied. We show that the ECD structural features are not always conserved among orthologs, suggesting that functions may have diverged in some OG sets. Moreover, we looked at targets of positive selection footprints in 12 pairs of OGs and noticed that depending on the subgroups, positive selection occurred more frequently either in the ECDs or in the KDs. (167 words)